STRUCTURAL AND FUNCTIONAL CHANGES OF THE HEART IN PATIENTS WITH ESSENTIAL HYPERTENSION AND CONCOMITANT FREQUENT EXTRASYSTOLES - Kuzminova, N.V.; Ivankova, A.V.; Ivanov, V.P.; Lozinsky, S.E.; Knyazkova, I.I.; Gavrylyuk, A.O. (World of Medicine and Biology, 2020)
The total of 156 patients (65 men and 91 women) with stage II hypertension (EH II) were examined, with an average age of 58.2 ± 0.9 years. The main clinical array consisted of 124 patients with frequent symptomatic supraventricular (SVE) (74 (59.7%) patients) or ventricular extrasystoles (VE) (50 (40.3%) pts) according to Holter monitoring of the electrocardiogram (HM ECG). The comparison group included 32 patients with EH II without cardiac arrhythmias. Echocardiographic evaluation of structural and functional changes of the heart showed that the presence of frequent extrasystoles was associated with an increase of right ventricular (RV) size and signs of its overload, more pronounced left ventricular hypertrophy (LVH), a significant decrease in LV systolic function and impaired myocardial relaxation with the prevalence of the rigid type of transmitral flow. Patients with EH II and frequent VE compared with patients with EH II and SVE had a more significant decrease in LV systolic function and more pronounced disorders of diastolic function, whereas patients with SVE had a more expressed LVH.
Keywords: arterial hypertension; essential hypertension; supraventricular extrasystole; ventricular extrasystole; echocardiography; Holter ECG monitoring